Effect of doses of nitrogen in the agronomy and physiology of yellow passion fruit - Rodríguez-Yzquierdo, Gustavo Adolfo; Pradenas-Aguila, Héctor Eduardo; Basso-de-Figuera, Carmen Amalia; Barrios-García, Marta; León-Pacheco, Rommel Igor; Pérez-Macias, Mercedes (Agronomía Mesoamericana, 2020)
Introduction. The passion fruit plant is important as fresh fruit and in the agroindustry, since its rich in minerals and vitamins and also has potential for domestic consumption and exportation. It has been shown that nitrogen (N) has an influence on fruit yield but there is no information on the optimal N range for maximum production. Objective. Determine the agronomic, physiological, and phenological response, yield and quality of fruit in the cultivation of parchita passion fruit against different doses of nitrogen. Materials and methods. At the Universidad Central de Venezuela, Maracay, Venezuela from April 2014 to march 2015, passion fruit plants were planted in a completely randomized design, six replicates, and six plants per experimental unit, a control (8 g N plant-1 (T1)) was evaluated and three doses of N (100 (T2), 200 (T3) and 300 (T4) g plant-1), an a dose of 50 and 300 g plant-1 of P2O5 and K2O, respectively were evaluated. The evaluated variables were: plant height, number of leaves, photosynthesis rate (A), transpiration (E), stomach conductance (Gs), chlorophyll index (CI), total leaf N content in doses at flowering and fruiting, yield, and fruit quality. Results. Higher doses of N obtained higher values in height, number of leaves, plant precocity, chlorophyll index, net photosynthesis, and foliar N content and lower values in T1. The variables Gs, A and E, did not show significant differences between the treatments. A 55 % yield reduction was obtained in the control treatment compared to the 200 g N plant-1 treatment which obtained the highest yield. The average fruit weight was significantly higher in T3. Conclusion. The best nitrogen dose in passion fruit plants was 200 g N plant-1.